2007
DOI: 10.1158/0008-5472.can-06-0850
|View full text |Cite
|
Sign up to set email alerts
|

Mice Lacking bi-1 Gene Show Accelerated Liver Regeneration

Abstract: The liver has enormous regenerative capacity such that, after partial hepatectomy, hepatocytes rapidly replicate to restore liver mass, thus providing a context for studying in vivo mechanisms of cell growth regulation. Bax inhibitor-1 (BI-1) is an evolutionarily conserved endoplasmic reticulum (ER) protein that suppresses cell death. Interestingly, the BI-1 protein has been shown to regulate Ca 2+ handling by the ER similar to antiapoptotic Bcl-2 family proteins. Effects on cell cycle entry by Bcl-2 family pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 47 publications
4
23
0
1
Order By: Relevance
“…21 We observed that NFATc1 was also already translocated to a much higher degree in BI-1-deficient splenocytes even without stimulation, similar to NF-κB ( Figure 3d) but unchanged at the expression level ( Figure 3e). These data corroborate results obtained in BI-1-deficient hepatocytes, which also showed an increased constitutive translocation of NFATc1, 12 and support the assumption that the changes in Ca 2+ signaling are responsible for the increased abundance and nuclear translocation (p65) shown by quantitative immunocytochemistry in BI-1 KO splenocytes. Splenocytes were stained with an α-RelA (p65) antibody and analyzed by confocal microscopy.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…21 We observed that NFATc1 was also already translocated to a much higher degree in BI-1-deficient splenocytes even without stimulation, similar to NF-κB ( Figure 3d) but unchanged at the expression level ( Figure 3e). These data corroborate results obtained in BI-1-deficient hepatocytes, which also showed an increased constitutive translocation of NFATc1, 12 and support the assumption that the changes in Ca 2+ signaling are responsible for the increased abundance and nuclear translocation (p65) shown by quantitative immunocytochemistry in BI-1 KO splenocytes. Splenocytes were stained with an α-RelA (p65) antibody and analyzed by confocal microscopy.…”
Section: Resultssupporting
confidence: 90%
“…This condition is caused by retention of proteins within the ER lumen, and in contrast to the UPR does not induce Grp78/BiP 23 which is also unchanged in the absence of BI-1. 12,13 Notably, NF-κB induction by the ER overload reaction can be attenuated by intracellular Ca 2+ chelators. 24,25 Therefore, both major functions of BI-1, its role in ER stress and in the maintenance of the intracellular Ca 2+ homeostasis, might be implicated in the observed phenotype.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, bax inhibitor-1 deficiency accelerates liver regeneration after PH, which is associated with an increase in cyclin D1 protein levels. 51 Akt can enhance expression of cyclin D1 through enhancing translation and inhibiting protein degradation. 52 Thus, the reduced expression of cyclin D1 is probably due to a decrease in Akt phosphorylation in HHcy mice.…”
Section: Discussionmentioning
confidence: 99%
“…When mice were exposed to hypoxic stress, the infarction size was significantly larger in bi-1 -/-than it was in bi-1 +/+ mice (Chae et al, 2004). Although one study found highly efficient regeneration of damaged liver in bi-1 knock-out mice (Bailly-Maitre et al, 2007), other studies have mainly focused on the protective functions of BI-1 in in vitro and in vivo systems (Bailly-Maitre et al, 2006;Chae et al, 2004;Dohm et al, 2006).…”
Section: +mentioning
confidence: 99%